Effect of the bath pH on the electrodeposition of nanocrystalline Pd-Co alloys and their magnetic properties - Noce, R. D.; Barelli, Nilso [UNESP]; Sumodjo, P. T. A.; Cornejo, D. R.; Benedetti, Assis Vicente [UNESP] (Elsevier B.V., 2006)
The effect of the bath pH on the electrodeposition of nanocrystalline Pd-Co alloys and on their magnetic properties was studied. The pH practically did not affect the alloy composition. Conversely, the pH showed a significant influence on the shape and size of crystallites. Two different crystallites morphology were observed depending on the bath pH. A crystallite size ranging from 18.2 to 30 nm was obtained from X-ray diffractometry (XRD) patterns using the Scherrer's method. Also from the XRD patterns the lattice strain percentage was calculated and correlated with the residual stress, which probably originated during the film electrodeposition on the substrate. Some alloy magnetic properties showed small variations. In contrast, high and unexpected coercivities were obtained reaching a maximum of 1.69 kOe at pH 5.5. The high coercivity values were attributed to the presence of residual stress at the film-substrate interface, which increased as the bath pH and crystallite size decrease, both of them contributing simultaneously to increase in coercivity. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Pd-Co alloys; pH effect; magnetic properties